The Holy See and the Creation of the prelature of Diamantino in Mato Grosso (1929): A Santa Sé e a criação da prelazia de Diamantino em Mato Grosso (1929) (Revista de História da UEG (REVHIST), 2023)
The objective of this article is to analyze the creation of the prelature of Diamantino, in 1929, a project of archbishop Francisco de Aquino Corrêa to reorganize the Archdiocese of Cuiabá. The proposal was processed between the years 1925 and 1929, being reformulated four times due to disagreements between the Mato Grosso episcopate over territorial limits. In this context, the Holy See intended to expand the number of ecclesiastical circumscriptions and ensure the presence of the Catholic Church among the indigenous populations, but it prized the unity of the episcopate and, therefore, disagreements should be overcome through diplomatic negotiations. It is intended to contribute to the studies on the creation of new ecclesiastical circumscriptions in Brazil, especially in Mato Grosso. The sources that allowed the research development were obtained from the Hemeroteca Digital and from the Vatican Apostolic Archives.Keywords: Holy See. Dioceses. Mato Grosso. Ecclesiastical Province of Cuiabá. Prelature of Diamantino.